Stabilization, Safety, and Security of Distributed Systems 12th International Symposium, SSS 2010, New York, NY, USA, September 20-22, 2010. Proceedings - Dolev, Shlomi; Cobb, Jorge; Fischer, Michael; Yung, Moti.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 12th International Symposium on Stabilization, Safety, and Security of Distributed Systems, SSS 2010, held in New York, USA, in September 2010. The 39 revised full papers were carefully reviewed and selected from 90 submissions. The papers address all safety and security-related aspects of self-stabilizing systems in various areas. The most topics related to self-* systems. The tracks were: self-stabilization; self-organization; ad-hoc, sensor, and dynamic networks; peer to peer; fault-tolerance and dependable systems; safety and verification; swarm, amorphous, spatial, and complex systems; security; cryptography, and discrete distributed algorithms.
Invited Talks Abstracts -- Arcane Information, Solving Relations, and Church Censorship -- Computation of Equilibria and Stable Solutions -- A Geometry of Networks -- Contributed Papers -- Systematic Correct Construction of Self-stabilizing Systems: A Case Study -- A Fault-Resistant Asynchronous Clock Function -- Self-stabilizing Leader Election in Dynamic Networks -- Loop-Free Super-Stabilizing Spanning Tree Construction -- A New Technique for Proving Self-stabilizing under the Distributed Scheduler -- A Tranformational Approach for Designing Scheduler-Oblivious Self-stabilizing Algorithms -- On Byzantine Containment Properties of the min?+?1 Protocol -- Efficient Self-stabilizing Graph Searching in Tree Networks -- Adaptive Containment of Time-Bounded Byzantine Faults -- Brief Announcement: Fast Convergence in Route-Preservation -- Authenticated Broadcast with a Partially Compromised Public-Key Infrastructure -- On Applicability of Random Graphs for Modeling Random Key Predistribution for Wireless Sensor Networks -- (3z(BSlow Is Fast(3y (Bfor Wireless Sensor Networks in the Presence of Message Losses -- Modeling and Analyzing Periodic Distributed Computations -- Complexity Issues in Automated Model Revision without Explicit Legitimate State -- Algorithmic Verification of Population Protocols -- Energy Management for Time-Critical Energy Harvesting Wireless Sensor Networks -- Stably Decidable Graph Languages by Mediated Population Protocols -- Broadcasting in Sensor Networks of Unknown Topology in the Presence of Swamping -- Brief Announcement: Configuration of Actuated Camera Networks for Multi-target Coverage -- Brief Announcement: On the Hardness of Topology Inference -- Self-stabilizing Algorithm of Two-Hop Conflict Resolution -- Low Memory Distributed Protocols for 2-Coloring -- Connectivity-Preserving Scattering of Mobile Robots with Limited Visibility -- Computing in Social Networks -- On Transactional Scheduling in Distributed Transactional Memory Systems -- Recursion in Distributed Computing -- On Adaptive Renaming under Eventually Limited Contention -- RobuSTM: A Robust Software Transactional Memory -- A Provably Starvation-Free Distributed Directory Protocol -- Lightweight Live Migration for High Availability Cluster Service -- Approximation of ?-Timeliness -- A Framework for Adaptive Optimization of Remote Synchronous CSCW in the Cloud Computing Era -- Chameleon-MAC: Adaptive and Self-? Algorithms for Media Access Control in Mobile Ad Hoc Networks -- A Comparative Study of Rateless Codes for P2P Persistent Storage -- Dynamically Reconfigurable Filtering Architectures -- A Quantitative Analysis of Redundancy Schemes for Peer-to-Peer Storage Systems -- A Framework for Secure and Private P2P Publish/Subscribe -- Snap-Stabilizing Linear Message Forwarding -- Vulnerability Analysis of High Dimensional Complex Systems -- Storage Capacity of Labeled Graphs -- Safe Flocking in Spite of Actuator Faults.s
Keywords: Computer science; Computer Communication Networks; Software engineering; Data protection; Computer software; Information Systems; Computer Science; Computer Communication Networks; Special Purpose and Application-Based Systems; Computation by Abstract Devices; Algorithm Analysis and Problem Complexity; Systems and Data Security; Management of Computing and Information Systems